IDENTIFICATION OF STUDENTS’ DIFFICULTY IN WRITING EXPOSITORY ESSAY - Fahmi Rizaldi; Mukrim Mukrim; Hastini Hastini (e-Journal of ELTS (English Language Teaching Society), 2022)
This study aims to identify English Education Study Program students’ writing problems and how they solve them in expository essays. Whether the problems that occurred may the students solve or not. The subjects of this research were 8 students of English Education Study Program. The research was a case study approach by applied qualitative. The instruments used to collect the data were tests and interviews. The result of data analysis showed that students struggle with generating ideas, vocabulary grammatical elements such as tenses, subject-verb agreement, spelling, and sentence structure while writing in English. To overcome those problems, students browsed on the internet to find other references, Grammarly to correct grammatical errors, and an electronic dictionary to translate Indonesian terms into English Terms. This implies that the students need to work on selecting the appropriate language for the subject of their writing.